2014
DOI: 10.1111/jgh.12447
|View full text |Cite
|
Sign up to set email alerts
|

The role of enhanced multi‐detector‐row computed tomography before urgent endoscopy in acute upper gastrointestinal bleeding

Abstract: Enhanced MDCT preceding urgent endoscopy may be an effective modality for the detection of bleeding origin in patients with acute upper GI bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Although not yet recommended by the international guideline (10) and the latest guidelines in Japan (20,21), the usefulness of non-contrast and contrast CT for UGIB has also been shown (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet recommended by the international guideline (10) and the latest guidelines in Japan (20,21), the usefulness of non-contrast and contrast CT for UGIB has also been shown (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the introduction of MDCT has led to increased image resolution and decreased scanning time [ 13 ], and this may be a useful modality for detecting bleeding foci in patients with massive GI bleeding. A previous study showed that MDCT had a moderate diagnostic accuracy in patients with non-variceal bleeding (50.2%); however, it had a diagnostic accuracy of 96.4% in patients with variceal bleeding [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the introduction of MDCT has led to increased image resolution and decreased scanning time [ 13 ], and this may be a useful modality for detecting bleeding foci in patients with massive GI bleeding. A previous study showed that MDCT had a moderate diagnostic accuracy in patients with non-variceal bleeding (50.2%); however, it had a diagnostic accuracy of 96.4% in patients with variceal bleeding [ 13 ]. Therefore, we evaluated the risk by adding CT scores to GBS, whereby 90% of patients who come to the ER from UGI bleeding are classified as high-risk, which we define as ‘evidence of active bleeding on MDCT, having liver cirrhosis or varix.’ Analysis of risk from GBS-CT showed a significant difference in transfusion amount according to the risk groups; however, the GBS score alone was insufficient to show this trend, as there was no blood transfusion in the low- and moderate risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, EGD has considerable limitations in the diagnosis of patients with massive bleeding or other co-morbidities, and often fails to assess the source of bleeding. In this aspect, MDCT was considered to be an outstanding diagnostic method due to its rapidity, spectrum of availability, and minimal invasiveness [ 14 – 16 ]. A prospective study of patients with UGIB who underwent EGD after MDCT showed that the sensitivity of this latter methodology to identify the location and the etiology of bleeding was 100% and 90.9%, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%